John Betjeman : reading the Victorians - Morse, Greg (Sussex Academic Press, 2021)
John Betjeman was the popular Poet Laureate since Tennyson. But beneath the modern window on Britain that he opened during his lifetime lay the influence of his nineteenth-century forbears. This book explores his identity through such Victorianism via the verse of that period, but also its architecture, religious faith and religious doubt.